A preliminary study of the impacts of alien Acacia infestation (A saligna) on the relative rates of nitrogen and phosphorus cycling in Lowland Fynbos, southwestern Cape, South Africa - Wienand, Karen Tania (Department of Biological Sciences, 2017)
This study was carried out on Sand Plain Lowland fynbos at Pella from April to September 1988. Environmental factors, nitrogen and phosphorus pool sizes and mineralization processes were investigated in the surface soils (1-10cm) of 7-8 year old fynbos vegetation and an adjacent Acacia saligna (Labill.) Wendl. infestation. While there was no significant difference in soil temperature between fynbos and acacia sites, soil moisture and organic matter content was significantly higher in the acacia soils. This favoured decomposition so that soil nutrient analyses showed enrichment of the soils (higher N and P) by the acacia infestation. Soil N and P mineralization was assayed using in situ incubations. Due to their higher soil total N concentrations, acacia soils showed greater inorganic N concentrations. In both acacia and fynbos soils ammonium was the dominant N form. This was ascribed to the high soil moisture content, while the low temperatures appeared to be the factor most strongly influencing ammonium accumulation. The low nitrate accumulations even in the field incubations indicated that the nitrification process was inhibited, probably by the high soil moisture content and low temperatures. The variable patterns of inorganic P accumulation were ascribed mainly to fluctuations between microbial mineralization and immobilization. Contrary to the hypothesis that the higher soil organic matter and greater concentrations of total N and Pin acacia soils would result in higher mineralization rates, there was no significant difference in the rates of N and P mineralization between fynbos and acacia soils. Thus, it was concluded that the higher decomposition rates in acacia soils was not associated with greater mineralization rates during the wet season (period of study).